Gas Chromatography–Mass Spectrometry Chemical Profiling and Radical Scavenging Potential of Sesquiterpene-Rich Essential Oil of Polygonum equisetiforme Sm.: In Silico Study on Hematopoietic Cell Kinase (Hck) and Human Peroxiredoxin 5 - Ahmed M. Abd-ElGawad; Rania F. Ahmed; Ahmed F. Essa; Abd El-Nasser G. El Gendy; Samah A. El-Newary; Abdelsamed I. Elshamy; Tushar C. Sarker; Yasser A. El-Amier (Chemistry, 2023)
Essential oils (EOs) are advised by traditional medical systems for the treatment of a variety of disorders worldwide. In many ancient medical systems around the world, Polygonum herbs have been employed as remedies including P. equisetiforme Sm. The EO profile of P. equisetiforme and its bioactivities have yet to be discussed in depth. As a result, the current study aims to investigate the chemical profile and free radical scavenging capacity of P. equisetiforme EO. Hydrodistillation was used to obtain the EO from P. equisetiforme, and gas chromatography–mass spectrometry (GC-MS) was used for analysis. A total of forty-three compounds, including terpenes and sesquiterpenes as the main components (76.13% and 69.06%, respectively), were identified in the oil using the GC-MS analysis. The main constituents of the oil were hexahydrofarnesyl acetone (29.45%), 7-epi-selinene (14.45%), isospathulenol (8.35%), and n-docosane (6.79%). The chemosystematic significance of the plant was established via multivariate assessing, comprising principal component analysis (PCA), hierarchical clustering, and constellation plot, of the EO principal components of the various Polygonum plants. The P. equisetiforme exhibited different associations with the studied Polygonum spp. Then, the scavenging of the free radicals 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) was used to evaluate the radical scavenging abilities of EO compared with those of vitamin C, a reference antioxidant. P. equisetiforme EO exhibited the scavenging capacity of the DPPH and the ABTS free radical with respective IC50 values of 470.01 and 113.74 mg L−1 compared with vitamin C, and with IC50 values of 39.06 and 26.09 mg L−1, respectively. The in silico studies revealed that the oxygenated sesquiterpenes, especially ar-turmerone, hexahydrofarnesyl acetone, and 5E,9E-farnesyl acetone, exhibited the best fitting with hematopoietic cell kinase (Hck) and human Peroxiredoxin 5 proteins with ΔG values of −6.14 and −4.93, −6.83 and −5.34, and −7.08 and −5.47 kcal/mol, respectively. The major components’ combined or individual effects may be responsible for the antioxidant properties. Therefore, additional extensive studies are advised to characterize the essential compounds as radical scavenger agents, either individually or in combination.